Konsumsi Daun Kelor (Moringa oleifera) dan Kadar Hemoglobin sebagai Faktor Risiko Kejadian Stunting pada Balita: Studi Case-Control: Association of Moringa oleifera Consumption and Hemoglobin Levels with Stunting among Children Under Five: A Case-Control Study - Tiasna, Apriani; Permatasari, Dian; Puspitasari, Dian Ika; Mayasari, Najhatin Eka; Ahmaniyah, Ahmaniyah (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Stunting remains a major public health problem that adversely affects physical growth, cognitive development, and future human capital. The condition is influenced by multiple factors, including hemoglobin status and nutritional intake. Moringa oleifera leaves are a locally available food source rich in protein, iron, vitamins, minerals, and antioxidants, making them a potential nutritional intervention to support child growth and prevent anemia. This study aimed to analyze the association between Moringa oleifera consumption, hemoglobin level, and stunting among children under five years of age in the working area of Banyuates Primary Health Center, Sampang Regency. A case-control study was conducted involving 80 children under five years of age registered from January to February 2026, consisting of 40 stunted children (case group) and 40 non-stunted children (control group). Participants were selected using purposive sampling. Data on Moringa oleifera consumption were collected using a structured questionnaire, while hemoglobin levels were obtained from primary health center medical records or the Maternal and Child Health (MCH) handbook. Stunting status was determined through height or length measurements using a calibrated microtoise stature meter with an accuracy of 0.1 cm and classified according to the WHO Child Growth Standards. Data were analyzed using the Chi-square test, and the magnitude of the associations was expressed as odds ratios (ORs) with 95% confidence intervals (CI) . Statistical significance was determined at p<0.05. The results demonstrated a significant association between Moringa oleifera consumption and stunting (p<0.001; OR=9.95; 95% CI: 2.87–34.53). Children who did not consume Moringa oleifera were almost ten times more likely to experience stunting than those who consumed it. Hemoglobin level was also significantly associated with stunting (p=0.032; OR=3.37; 95% CI: 1.07–10.61), indicating that anemic children had a higher likelihood of being stunted than non-anemic children. Consumption of  Moringa oleifera and hemoglobin level were significantly associated with stunting among children under five. Promoting the utilization of Moringa oleifera as a nutrient-rich local food and strengthening early anemia screening may contribute to stunting prevention strategies in primary health care settings.